2014
DOI: 10.1016/j.jplph.2013.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Germination of salt-stressed seeds as related to the ethylene biosynthesis ability in three Stylosanthes species

Abstract: Stylosanthes, a genus of tropical forage legume, is known to exhibit good persistence in saline soils, yet mechanisms for regulation of seed germination under salt stress are poorly understood. This study was carried out to evaluate the mode of action of salt stress on seed germination of Stylosanthes. 1-Aminocyclopropane-1-carboxylic acid (ACC) increased ethylene biosynthesis and germination of NaCl-inhibited seeds in a dose-dependent manner. Contents of ACC and germination of Stylosanthes humilis seeds incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 41 publications
1
27
0
Order By: Relevance
“…These results could be explained by the effect of ET in overcoming the inhibitory effect of ABA in seed germination (Kucera et al, 2005). Similarly, alleviation of the detrimental effects of salinity on seed germination by ET has been shown in numerous species (Mohammed, 2007 Recently, Silva et al (2014) developed interesting experiments to analyse the role of endogenous ET in seed germination. This study confirmed that JERF3 expression in tobacco plants enhanced adaptation to osmotic stress, which suggests a possible role of ET in germination under drought stress.…”
Section: Ethylene (Et)mentioning
confidence: 94%
“…These results could be explained by the effect of ET in overcoming the inhibitory effect of ABA in seed germination (Kucera et al, 2005). Similarly, alleviation of the detrimental effects of salinity on seed germination by ET has been shown in numerous species (Mohammed, 2007 Recently, Silva et al (2014) developed interesting experiments to analyse the role of endogenous ET in seed germination. This study confirmed that JERF3 expression in tobacco plants enhanced adaptation to osmotic stress, which suggests a possible role of ET in germination under drought stress.…”
Section: Ethylene (Et)mentioning
confidence: 94%
“…Salinity stress inhibits the growth of plants at early seedling and developed seedling stages (Ferdose et al, 2009;Silva et al, 2014). In this study, the impact of saline irrigation water on germination and early growth stages were studied.…”
Section: Discussionmentioning
confidence: 99%
“…Salinity tolerance is a complex trait that can be improved through integration between molecular geneticists and physiologists . Enormous amount of researches have explored the molecular and physiological mechanism of salinity stress, however, we are still far from understanding the key traits that confer such tolerance (Bartels and Sunkar, 2005;Silva et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The atmosphere of the flask was mixed occasionally with a long needle syringe. Following an 18-h incubation, a sample of 1 mL was taken from the flask headspace with a syringe and the ethylene concentration was measured by gas chromatography as described by Silva et al (2014).…”
Section: Determination Of Ethylene Levelsmentioning
confidence: 99%